The Influence of Biographical Factors on Adult Learner Self-Directedness in an Open Distance Learning Environment - Botha, Jo-Anne; Coetzee, Mariette (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
This study investigated the relationship between self-directedness (as measured by the Adult Learner Self-Directedness Scale) and biographical factors such as age, race, and gender of adult learners enrolled at a South African open distance learning (ODL) higher education institution. Correlational and inferential statistical analyses were used. A stratified random sample of 1,102 mainly black and female learners participated in the study. The Adult Learner Self-Directedness Scale (ALSDS) identified four constructs of adult learner self-directedness in an Open Distance Learning Higher Education (ODLHE) milieu, namely the strategic utilisation of officially provided resources, engaged academic activity, success orientation for ODLHE, and academically motivated behaviour. The research indicated that significant differences exist between the gender, race and age groups with regard to self-directedness. With regard to gender, males scored significantly higher than females on success orientation for ODLHE and engaged academic activity. With regard to race, Indian participants scored significantly higher than the other race groups on strategic utilisation of officially provided resources and engaged academic activity. The white participants scored significantly higher than the other race groups on success orientation for ODLHE. In terms of age, the age group >50 scored significantly higher than the other age groups on success orientation for ODLHE and self-efficacy. In terms of success orientation, the means for the age groups seem to increase as the ages of participants increase. The age group 18-25 scored significantly higher than the other age groups on engaged academic activity.